Anti-inflammatory effects of nicotine in obesity and ulcerative colitis - Kirchgessner Annette; Lakhan Shaheen E (Journal of Translational Medicine, 2011)
Abstract Cigarette smoke is a major risk factor for a number of diseases including lung cancer and respiratory infections. Paradoxically, it also contains nicotine, an anti-inflammatory alkaloid. There is increasing evidence that smokers have a lower incidence of some inflammatory diseases, including ulcerative colitis, and the protective effect involves the activation of a cholinergic anti-inflammatory pathway that requires the α7 nicotinic acetylcholine receptor (α7nAChR) on immune cells. Obesity is characterized by chronic low-grade inflammation, which contributes to insulin resistance. Nicotine significantly improves glucose homeostasis and insulin sensitivity in genetically obese and diet-induced obese mice, which is associated with suppressed adipose tissue inflammation. Inflammation that results in disruption of the epithelial barrier is a hallmark of inflammatory bowel disease, and nicotine is protective in ulcerative colitis. This article summarizes current evidence for the anti-inflammatory effects of nicotine in obesity and ulcerative colitis. Selective agonists for the α7nAChR could represent a promising pharmacological strategy for the treatment of inflammation in obesity and ulcerative colitis. Nevertheless, we should keep in mind that the anti-inflammatory effects of nicotine could be mediated via the expression of several nAChRs on a particular target cell.